Penilaian Kinerja Keuangan Koperasi Serba Usaha Sion Sejahtera Di Kabupaten Konawe Sulawesi Tenggara - Mantouw, Avenia Princessa Evangelistha; Tangkere, Ellen G.; Pangemanan, Paulus A. (Sam Ratulangi University, 2023)
The study aims to evaluate Financial Performance of Koperasi Serba Usaha Sion Sejahtera. The data collection method used in this study used primary and secondary data. The data are used financial statements of balance sheet and calculation of the remaining results of operations from 2017 to 2021. Data measured based on 7 aspects namely capital, quality of earning assets, management, efficiency, liquidity, independence and growth, and cooperative identity. Data is measured with ratio analyzed based on Peraturan Kementerian Koperasi dan Usaha Kecil Menengah Republik Indonesia Nomor 06/Per/Dep.6/IV/2016. The results showed that financial performance of Koperasi Serba Usaha Sion Sejahtera in 2017 obtained a value of 81,40 and went up to 82,90 in 2018 so that it was categorized are healthy. Whereas in 2019 the value obtained was 79,65 and decreased to 77,90 in 2020 and in 2021 the value dropped to 75,90 so that it was categorized are quite healthy.